1987
DOI: 10.2307/1911270
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Sets of Estimates for Regressions with Correlated or Uncorrelated Measurement Errors in Arbitrary Subsets of all Variables

Abstract: We consider the single equation errors-in-variables model and assume that a researcher is willing to specify an upper bound on the variance covariance matrix of ineasurement errors in the endogenous and exogenous variables. The measurement errora may show any pattern of correlations. It is shown tha[ as a result the set of ML estimates is bounded by an ellipsoid. When, in addition, the variance covariance matrix of the errors is constrained to be diagonal, the set of ML estimates is shown to be bounded by [he … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…For these reasons, we focus on labor productivity of individual mines, and develop methods that take into account heterogeneity in the data. 4 We model labor productivity separately for groups of mines de¯ned by regional location and overall type of technology. Mine-speci¯c¯xed e®ects are included to further capture the myriad of heterogeneous features (geology and di®erent types of capital con¯guration), and time e®ects are included to capture group-wide productivity variation.…”
Section: -1995mentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, we focus on labor productivity of individual mines, and develop methods that take into account heterogeneity in the data. 4 We model labor productivity separately for groups of mines de¯ned by regional location and overall type of technology. Mine-speci¯c¯xed e®ects are included to further capture the myriad of heterogeneous features (geology and di®erent types of capital con¯guration), and time e®ects are included to capture group-wide productivity variation.…”
Section: -1995mentioning
confidence: 99%
“…Coal output is measured in clean short tons, and for aggregating 4 We discuss many of the salient aspects of our data below. See Ellerman, Stoker and Berndt (1999) for more details on the construction of our data.…”
Section: Data Speci¯csmentioning
confidence: 99%
“…Bekker et al (1987) discuss the case of errors in regressors and the regression error being correlated. Iwata (1992) and Pratt (1986, 1987) show that bounds on these correlations may help find bounds on parameters of interest.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that no informative bounds on the parameters of interest exist when measurement error is correlated with both the latent regressor and the error of the regression (Krasker and Pratt, 1986;Bekker et al, 1987;Erickson, 1989). Therefore, additional information is needed to find the bounds on the parameters of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Even under non-identification, bounds on the parameters can be established from the distribution of the observable variables [see Fuller (1987, p. 11)]. These bounds may be wide or narrow, depending on the covariance structure of the variables; see, e.g., Klepper and Leamer (1984) and Bekker et al (1987). 2 The last two assumptions are stronger than strictly needed; time invariance of E(α i v it ) and E(α i u it ) is sufficient.…”
mentioning
confidence: 99%